WATER BALANCE STUDIES IN MICRO-WATERSHEDS OF UPPER DAMODAR VALLEY - Reddy, K.S.; Bhattacharya, A.K.; Rao, K.V.R. (Journal of Soil and Water Conservation, 2022)
A 20 year seasonal rainfall data was used to estimate the runoff, spill volumes and storage volumes’ of water In the small reservoirs of micro-watersheds by using surface water yield Model (SWYMOD), The weekly gross water deficits/ surplus were estimated by using water balance equation for three different crop activities viz. paddy, maize and pigeon pea. The paddy crop has deficits during entire period of its growing at 75% probability. The maximum gross water deficit of 65.1 mm was noticed in 39’" week during critical stage of flowering to maturity, For maize crop, the maximum deficit of 16.5 mm was seen in 34m week during grain filling stage. Rut, the pigeon pea has got no deficits during its critical stages of growth. By matching total water available in the reservoirs and gross water deficits at 75% probability indicated that, with the intensive irrigation strategy the maximum area of 2.83 ha for paddy, 18.69 ha for maize and 19.02 ha for pigeon pea could be brought under irrigation when these are considered mutually exclusive activities. However, after paddy and maize, an area of 16.29 ha and 0.33 ha could be brought under little millet as rainfed crop in the selected micro-watersheds.